2019
DOI: 10.3390/toxins11090527
|View full text |Cite
|
Sign up to set email alerts
|

Naja atra Cardiotoxin 3 Elicits Autophagy and Apoptosis in U937 Human Leukemia Cells through the Ca2+/PP2A/AMPK Axis

Abstract: Cardiotoxins (CTXs) are suggested to exert their cytotoxicity through cell membrane damage. Other studies show that penetration of CTXs into cells elicits mitochondrial fragmentation or lysosome disruption, leading to cell death. Considering the role of AMPK-activated protein kinase (AMPK) in mitochondrial biogenesis and lysosomal biogenesis, we aimed to investigate whether the AMPK-mediated pathway modulated Naja atra (Taiwan cobra) CTX3 cytotoxicity in U937 human leukemia cells. Our results showed that CTX3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Structural and functional analyses have suggested that the interaction of CTXs with the membrane is mediated through the tips of loops I/II, and that the basic residues flanked by hydrophobic patch at loop I/II regions are involved in the membrane-permeabilizing activity of CTXs [2,4,6,8]. In agreement, previous studies have reported that modification of the conserved Met residues at loop II of CTXs causes a drastic drop in their membrane-damaging activity [16].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Structural and functional analyses have suggested that the interaction of CTXs with the membrane is mediated through the tips of loops I/II, and that the basic residues flanked by hydrophobic patch at loop I/II regions are involved in the membrane-permeabilizing activity of CTXs [2,4,6,8]. In agreement, previous studies have reported that modification of the conserved Met residues at loop II of CTXs causes a drastic drop in their membrane-damaging activity [16].…”
Section: Discussionsupporting
confidence: 76%
“…Collectively, these results indicate that the intact Asp29 may functionally modulate the membrane-interacting mode of CTX1, thereby hindering the performance of CTX1 with highly disruptive membrane activity. However, loop I of S-type CTXs has been suggested to be crucial for their binding with zwitterionic phospholipids [4,6]. Gorai et al [6] proposed that loop II of S-type CTXs is the structural region chiefly governing complex formation of proteins with PC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PP2A inactivation is regarded as the most important molecular event that causes abnormal tau hyperphosphorylation in the AD brains (Iqbal, Liu, & Gong, 2016). PP2A‐C expression can be inhibited by increased intracellular [Ca 2+ ] i through degradation (Chiou et al, 2019) and activated ER stress (Tay et al, 2012). Therefore, the reduction of PP2A‐C in hTau‐overexpressing neurons may be caused by activated ER stress and elevated intraneuronal [Ca 2+ ] i .…”
Section: Discussionmentioning
confidence: 99%